Assessment of different induction chemotherapy regimens in locally advanced nasopharyngeal carcinoma: Meta‐analysis. Issue 8 (31st March 2021) - Guan, Hui; He, Yan; Su, Yonglin; Wei, Zhigong; Liu, Zheran; Wang, Jingjing; He, Ling; Mu, Xiaoli; Li, Ruidan; Hu, Xiaolin; Peng, Xingchen
Abstract: Background: A Bayesian network meta‐analysis was performed to compare the efficacy and toxicities among different induction chemotherapy regimens in locally advanced nasopharyngeal carcinoma (LA‐NPC). Methods: Electronic databases were searched for literature up to September 16, 2019. Two researchers independently selected the articles, evaluated the quality of the literature, and extracted and analyzed the data. Results: There were no significant differences in survival outcomes, mucositis, or gastrointestinal adverse events among the four regimens. The probability of GP being the best induction scheme to improve OS was 43.7%. The completion rate of concurrent chemotherapy with the GP regimen was significantly reduced than the other three regimens. Conclusions: The survival outcomes of the four regimens in LA‐NPC were comparable. Considering only OS, GP showed the highest probability of improving the survival of LA‐NPC, while it also affected the completion of concurrent chemotherapy.